Respuesta :
Before trying to write it other way then it is now first lets just solve it quickly
(7/8)x + (3/4) = -6
(7/8)x = -6-(3/4) "Lets keep them in this form and not take them in points"
(7/8)x = -(27/4)
x = -(27/4)/(7/8)
x = -54/7 or 7.714
now to another way:
(7/8)x+3/4=-6
Put some LCM Magic there
(7x+6)/8=-6
7x+6=-(6)(8)
7x+6=-48
7x+54=0
(7/8)x + (3/4) = -6
(7/8)x = -6-(3/4) "Lets keep them in this form and not take them in points"
(7/8)x = -(27/4)
x = -(27/4)/(7/8)
x = -54/7 or 7.714
now to another way:
(7/8)x+3/4=-6
Put some LCM Magic there
(7x+6)/8=-6
7x+6=-(6)(8)
7x+6=-48
7x+54=0